Foreign national prisoners, discrimination and race relations in Irish prisons - Doyle, David M. (Journal of criminology, 2024)
Recent reports have highlighted the discriminatory treatment endured by foreign national prisoners (FNPs) in particular Irish prisons, but one key voice has been relatively absent from the discourse to date – the perspectives of the prisoners themselves. This article aims to complement these “top-down” perspectives with a comprehensive “bottom-up” analysis rooted in the experiences of 82 FNPs and explore the extent to which they were subject to racism, discrimination and differential treatment by prison staff and fellow inmates across eight Irish prisons. The article begins by outlining the methodology of the qualitative study. It then presents our findings in two parts. The first part focuses on FNPs’ personal views of their relationships with staff in Irish prisons. The second part explores the extent to which these FNPs interact with Irish prisoners and prisoners from other jurisdictions. The article reveals that forming relationships with staff and fellow inmates is challenging for certain FNPs due to racial prejudice, language barriers and segregation based on nationality.